2019
DOI: 10.1182/blood-2018-03-839993
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule BCL6 inhibitor effectively treats mice with nonsclerodermatous chronic graft-versus-host disease

Abstract: Patient outcomes for steroid-dependent or -refractory chronic graft-versus-host diesease (cGVHD) are poor, and only ibrutinib has been US Food and Drug Administration (FDA) approved for this indication. cGVHD is often driven by the germinal center (GC) reaction, in which T follicular helper cells interact with GC B cells to produce antibodies that are associated with disease pathogenesis. The transcriptional corepressor B-cell lymphoma 6 (BCL6) is a member of the Broad-complex, Tramtrack, and Bric-abrac/poxvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…BR→BALB/c model of scleroderma, a disease that is principally attributed to Th17 alloimmunity and not autoantibody (52). These data are consistent with previous work in which we showed that a small-molecule BCL6 peptidomimetic functioned as a potent inhibitor in the BOS model but had no effect in the same scleroderma system, as reported in this manuscript (25). Coupled with the observations that pharmacological syk inhibition potently affects Tfh cell-dependent chronic GvHD in mice and is efficacious in human chronic GvHD, yet has little clinical benefit in the scleroderma model (53), our findings suggest that C5aR1 inhibition preferentially restrains Tfh cell-dependent GC formation when administered after disease initiation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…BR→BALB/c model of scleroderma, a disease that is principally attributed to Th17 alloimmunity and not autoantibody (52). These data are consistent with previous work in which we showed that a small-molecule BCL6 peptidomimetic functioned as a potent inhibitor in the BOS model but had no effect in the same scleroderma system, as reported in this manuscript (25). Coupled with the observations that pharmacological syk inhibition potently affects Tfh cell-dependent chronic GvHD in mice and is efficacious in human chronic GvHD, yet has little clinical benefit in the scleroderma model (53), our findings suggest that C5aR1 inhibition preferentially restrains Tfh cell-dependent GC formation when administered after disease initiation.…”
Section: Discussionsupporting
confidence: 92%
“…Coupled with the observations that pharmacological syk inhibition potently affects Tfh cell-dependent chronic GvHD in mice and is efficacious in human chronic GvHD, yet has little clinical benefit in the scleroderma model (53), our findings suggest that C5aR1 inhibition preferentially restrains Tfh cell-dependent GC formation when administered after disease initiation. These observations build upon prior murine studies in which chronic GvHD could be reversed by targeted GC disruption using a lymphotoxin-β fusion protein (54) or administering T cells or bone marrow as a source of B cells defective in supporting GC formation (25,43,(53)(54)(55). Relevant to human chronic GvHD patients, serum CXCL13 levels are elevated (44) and are associated with low Tfh cell numbers in peripheral blood (44,53), suggesting that circulating Tfh cells have been recruited into GCs where high-affinity antibody-secreting cells can be generated.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…6A). To inhibit Tfh cell responses, we used the small-molecule inhibitor 79-6, which inhibits transcription factor Bcl6 (39,40). Treatment with 79-6 decreased IL21 production in IL4-and DTA-1stimulated na€ ve CD4 þ T cells without inducing cellular cytotoxicity ( Fig.…”
Section: Il4 Is Required For Dta-1-induced Il21-producing Tfh Cellsmentioning
confidence: 99%